Evolution of the collaborative innovation network in the Korean ICT industry: a patent-based analysis. Issue 2 (1st February 2023) - Hwang, Inyoung
ABSTRACT: This study explores the evolutionary mechanisms of the inter-firm collaborative innovation network in the Korean ICT industry, focusing on inter-firm homophily. Using firm network data based on a joint patent from 1980 to 2015, this study reveals that firms participate in collaborative innovation primarily to complement their technological resources. Also, the collaborative innovation network among Korean ICT firms has evolved mainly by homophily mechanisms and has limited expandability. The findings suggest that the government can promote SMEs' participation in collaborative innovation by concentrating on supporting the development of technological capabilities.